Subsurface Utility Identification at ITERA Campus Using Multi-frequency Ground Penetrating Radar - Andri Yadi Paembonan; Fedy Darma Wijaya Waruwu (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Infrastructure development at the Sumatra Institute of Technology is growing rapidly, hence, it requires new utilities installation network such as cables and pipes to supply electricity and clean water. Installing new utility line, it is necessary to secure and know the existence and depth of the previously embedded utility network to avoid damage that could hamper the construction process or cause large losses. Accessing the sub-surface information, geophysical method, such as Ground Penetrating Radar (GPR) can be utilized for identifying buried utility networks, ensuring the safe installation of new utilities and preventing damage to existing embedded utilities. In this study, a GPR device with a frequency range 40 MHz-3.4 GHz comprising 5 tracks was employed. The acquired data underwent processing using GPR Insights software, generating a radargram cross-section that provides information about the subsurface.The results from the radargram reveal a hyperbolic reflection anomaly, signifying the presence of a utility network beneath the surface, suspected to be pipe and cable utilities. The utility network is detected at varying depths of 0.5 m, 0.8 m, 1 m, and 1.2 m at different distances. Furthermore, several anomalies in the form of hyperbolas are observed, suggesting potential utilities due to their continuity with other paths.